2007
DOI: 10.1080/13607860600735887
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive plasticity in people at risk for dementia: Optimising the testing-the-limits-approach

Abstract: A topic of great interest in gerontology research is the prediction of cognitive deterioration which marks the transition from mild cognitive impairment (MCI) to dementia. In this area, the term cognitive plasticity can be of great interest. We examined the utility of the Adaptive Figure Series Learning Test (ADAFI) to evoke cognitive plasticity and to show whether reduced plasticity can be found in people with MCI. In a pre-test-intervention-post-test design, intervention with the ADAFI was compared to an uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
3
9
0
1
Order By: Relevance
“…These results are in accordance to Schreiber and Schneider,43 who indicate that plasticity-oriented information given in a pre-test-training-post-test-design is potentially useful for the purposes of early identification of dementia, and to Lindenberg and Reschies,20 who found that mildly demented individuals, with a lower baseline that those “normal” individuals, show similar gains through learning.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in accordance to Schreiber and Schneider,43 who indicate that plasticity-oriented information given in a pre-test-training-post-test-design is potentially useful for the purposes of early identification of dementia, and to Lindenberg and Reschies,20 who found that mildly demented individuals, with a lower baseline that those “normal” individuals, show similar gains through learning.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with research showing that individuals with MCI show learning potential and cognitive plasticity (Akhtar et al 2006; Schreiber and Schneider 2007), these findings indicate that CRTs can effectively change targeted behaviors, knowledge, and beliefs in older adults with MCI, that adults with MCI are teachable, and that additional CRT trials are warranted with this population.…”
Section: Discussion: Summary and Future Directionssupporting
confidence: 80%
“…This could reflect application of learned memory strategies during memory test performance. Alternately, general stimulation provided by the intensive intervention may have facilitated cognitive plasticity, which has been documented in other studies with MCI individuals (Huckans et al, 2013;Schreiber & Schneider, 2007;Simon, Yokomizo, & Bottino, 2012).…”
Section: Discussionmentioning
confidence: 95%